Tunneling of Hydrogen and Deuterium Atoms on Interstellar Ices (Ih and ASW) - Nyman, Gunnar (Frontiers in Astronomy and Space Sciences, 2021)
Simplistic models are used to theoretically investigate the kinetic isotope effect of hydrogen and deuterium atom diffusion on hexagonal ice and amorphous solid water. Comparisons with experimental results by Kuwahata et al. (2015) at 10 K are made. The experimentally derived kinetic isotope effect on amorphous solid water is reproduced by transition state theory. The experimentally found kinetic isotope effect on hexagonal ice is much larger than on amorphous solid water and is not reproduced by transition state theory. Additional calculations using model potentials are made for the hexagonal ice, but the experimental kinetic isotope effect is not fully reproduced. A strong influence of temperature is observed in the calculations. The influence of tunnelling is discussed in detail and related to the experiments. The calculations fully support the claims by the Kuwahata et al. that on amorphous solid water the diffusion is predominantly by thermal hopping while on the polycrystalline ice tunnelling diffusion contributes significantly.